Types And Classification of The Most Common Weeds Found In Unused (Dry) Lands - Muminova, Turdieva Nilufar; Majitovna, Qalandarova Maftuna; Qobil, Murtazaev; Abdumalik ugli, Yuldoshev Abduaziz; Akbarovna, Togaeva Dilnura (American Journal of Biodiversity, 2026)
Weeds have a high seed germination capacity and develop more rapidly than cultivated crops. Once established, weeds compete with crops for soil moisture and nutrients and create shading, thereby suppressing the growth of the main crop. In addition, weeds growing along irrigation ditches, roadsides, and field margins serve as primary reservoirs for the overwintering, reproduction, and development of agricultural pests and diseases.